El cuento como transmisor de valores: "Warm Fuzzy Tale" y "Le conte chaud et doux des chaudoudoux" - Mª José Bonachía; Julieta Ojeda; Mª Luz Oyón (Universidad de La Rioja, 2013)
The transmission of ethical and social values through the contents of a syllabus is one of the objectives of the Spanish "Reforma" (a major revision of the national syllabus done by the Spanish Ministry of Education). Second language teachers can and must contribute to the implementation of these principles in their classroom by simply choosing appropriate material. Tales are some of the teaching material most often used in second language classrooms and are a perfect means for the transmission of these values. Claude Steiner's story "Warm Fuzzy Tale" and its French adaptation, "Le conte chaud et doux", base their argument on the need for love that all human beings have. In this article the values in this story are analysed in both the Original and the French version as conveyed by means of the plot and the illustrations in the two different versions.